Perspectivas de desenvolvimento local e comercialização na comunidade do Rincão do 28 Alegrete, RS, Brasil - Martínez, Yosani Morales (2017)
The central theme is focused on the association of cattle producers in the community of Rincão do 28 in Alegrete, RS. The objective was to analyze the association of the local development perspectives and the market accesses related to beef cattle ranching, with livestock farming being an important activity in Rio Grande do Sul, occupying the state sixth place in production in Brazil. For the study, a documentary with the topics of geographical indications and initiatives of local groups as local development tools was carried out. Thus, we also analyzed some breed associations within the state, such as Angus; Hereford and Braford, which together with the refrigeration industry are engaged in the marketing of processed meat. Other marketing options were also considered, such as the Geographical Indication: Meat of the Pampa Gaúcho of the Southern Campaign and the seal of the Alianza del pastizal association, all of which are a source of income in which producers obtain a remuneration in the sale of the animals. Once these issues have been addressed, I have had a sense of local development, geographical indications and how distinctive seals contribute as an asset to the marketing of products, in this case, livestock. The information was compiled through a case study methodology in its single case modality, carried out in two moments: the first part was the bibliographic research (documentary) with the aforementioned themes, and the field research with the Interviews with ten of the association's producers. The results obtained in the field research showed how the association intervened in the increase of production; How it accelerated the arrival of public policies in the installation of electric light and the improvement of the highway; As well as in social issues such as the incorporation of women in decision making in the production part, thus observing prospects for local development through the association and showing that there are capacities and the willingness to improve production and market niches , As well as considering new options as a geographical indication, but in this case for another type of production such as sheep.